Factors affecting consumers’ decision making process in Purchasing safe street food in Nakhon Si Thammarat Province, Thailand - Khongtong, Jatuporn (2016)
Nakhon Si Thammarat (NST) province is one of the cities in Thailand that offers various types of street foods. However, the number of street vendors that the food was certified safe is very low, and there are many consumers who still purchase street food because of their lifestyle. As a result, the consumers may get effect from food risk. Therefore, this research aims to evaluate the significant factors that influence consumers’ decision-making process on safe street food purchasing. The objectives of this research are to identify the individual factor that influences their decision making process, to examine the effects of each variables on each level of consumers’ decision making process, and to evaluate the effectiveness of food safety certification on consumers’ purchasing. Quantitative method was used to examine the influence of various factors on decision making process based on the decision making model of Engel-Miniard-Blackwel (EMB) as well as the Utility Function Theory. Structural Equation Model (SEM) results showed all factors affected the variables in consumers’ decision-making process; the consumers’ motivation (MOTI) affected every stage of the process, the consumers’ food safety knowledge (KNOW) affected the consumers’ need recognition in purchasing safe street food (NEED) and the consumers’ pre-purchase evaluation (PREP) and the consumers’ convenience foodpurchasing lifestyle (LIFE) affected only consumers’ safe food purchasing (PURC). In addition, the variable of the decision making in one stage also affected each variable in the next stage, such as, NEED→PREP, and PREP→PURC. Furthermore, the consumers’ attitude towards food safety certification (CERT) could not moderate PREP→PURC. This study can be utilized by the authorities in order to understand the significant factors when developing strategies that may encourage consumers to purchase safe street food, including effective procedures to promote the food safety certificate. Future study can examine what other factors that might influence consumers’ safe street food purchasing.